(untitled) - Loksova, Zuzana (Doprava a spoje, 2007)
All up to date experiences of countries with advanced free-market economies suggest, that those transport companies are successful which perform active market policies and offer always reliable and comfortable transportation. It means that negative image of public conveyances can be avoided only by active marketing policies and consistent orientation towards customer requirements.